Technical graphics communication. - Bertoline, Gary R., ....-; Wiebe, Eric N., ....- (Boston : McGraw-Hill, 2003)
1.Visual science for technical graphics 2.Fundamentals of technical graphics 3.Descriptive geometry 4.Standard technical graphics practices 5.Technical graphics in industry
Keywords: CAD systemen; Computer graphics; Computertoepassingen; Grafische communicatie; Technisch tekenen